THE EFFECT OF ACNE VULGARIS ON BODY IMAGE, SELF-ESTEEM, AND SELF-CONFIDENCE AMONG ADOLESCENTS - Ayu Chintya, Shally; Nafiah Apriliasiharta; Siti Khomsatin (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Acne vulgaris, or acne, is a common skin problem among adolescents, primarily due to hormonal, physical, psychological, and social changes. This study aims to analyze the impact of acne on body image, self-esteem, and self-confidence among adolescents in Islamic boarding schools. A quantitative method with a case-control design was used on 170 respondents (90 cases, 80 controls). The research instruments included the BAS-2 for body image, the GSES for self-confidence, and the RSES for self-esteem. Analysis was conducted using the chi-square test (95% CI) and path analysis. The results showed that acne directly affected body image (b=0.64; p=0.042), self-esteem (b=-1.16; p=0.001), and self-confidence (b=-0.70; p=0.045). Indirectly, body image affected self-esteem, and self-esteem affected self-confidence. These findings confirm that acne has a significant impact on the psychological aspects of adolescents, thus requiring special attention in efforts to improve mental health and social support.adolescents. Body image indirectly influence self-confidence through self-esteem, and self-esteem also has an indirect effect through self-confidence.